Assessment of the Infectious Status of Transmissible Transfusion Infections (Hepatitis B and C) among β- Thalassemia Major Patients of Karachi; A Multicenter Study by SBTA (Sindh Blood Transfusion Authority) - Hira Afreen, Mehreen Sheikh, Dur E Naz Jamal, Hooma Ourooj Butt, Maeesa Wadood, Aziz Ali (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Transfusion-transmitted infections such as Hepatitis B and C are a great health concern to blood safety as they are associated with significant morbidity and mortality. Multi-transfused patients like Beta Thalassemia Major patients are particularly vulnerable to the fatal consequences of these blood-borne diseases. Early diagnosis and prompt treatment will improve the quality of life of these patients. Objective: The study was intended to determine the prevalence of HBV and HCV, using Real-time Quantitative Polymerase Chain Reaction among registered Beta Thalassemia Major patients in various thalassemia centers of Karachi. Method: six month cross-sectional study was conducted in Karachi following the ethical approval of the Sindh blood transfusion authority (SBTA). A total of 328 multi-transfused Beta Thalassemia Major patients were enrolled in the study from eight different facility centers in Karachi. The. All patients were screened for Hepatitis B surface antigen (HBsAg) and Anti-Hepatitis C antibodies (HCV) using enzyme-linked immunosorbent assay (ELISA). HCV RNA was detected of all reactive anti HCV samples and HBV DNA of HbsAg reactive samples using real time PCR. Results: Out of 328 study participants, 282 showed serological reactive initially for Anti HCV antibodies and 52 patients were reactive for Hepatitis B Surface Antigen (HBsAg). Among the HCV positive screened females 82 have positive PCR results, while 95 males have positive PCR result. Among the HBV positive screened females 18 have positive PCR results, while 10 males have positive PCR result. Practical Implication: this study will help to determine the prevalence of HCV, HBV in thalassemia patients. Conclusion: This study concluded that hepatitis Cis the most common transfusion-transmitted infection (TTIs) among transfusion-dependent β-thalassemia major patients. Keywords: transfusion-transmitted infection, HCV, HBV, Thalassemia